-7(v+3)+3v+7=6v+6

Simple and best practice solution for -7(v+3)+3v+7=6v+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7(v+3)+3v+7=6v+6 equation:


Simplifying
-7(v + 3) + 3v + 7 = 6v + 6

Reorder the terms:
-7(3 + v) + 3v + 7 = 6v + 6
(3 * -7 + v * -7) + 3v + 7 = 6v + 6
(-21 + -7v) + 3v + 7 = 6v + 6

Reorder the terms:
-21 + 7 + -7v + 3v = 6v + 6

Combine like terms: -21 + 7 = -14
-14 + -7v + 3v = 6v + 6

Combine like terms: -7v + 3v = -4v
-14 + -4v = 6v + 6

Reorder the terms:
-14 + -4v = 6 + 6v

Solving
-14 + -4v = 6 + 6v

Solving for variable 'v'.

Move all terms containing v to the left, all other terms to the right.

Add '-6v' to each side of the equation.
-14 + -4v + -6v = 6 + 6v + -6v

Combine like terms: -4v + -6v = -10v
-14 + -10v = 6 + 6v + -6v

Combine like terms: 6v + -6v = 0
-14 + -10v = 6 + 0
-14 + -10v = 6

Add '14' to each side of the equation.
-14 + 14 + -10v = 6 + 14

Combine like terms: -14 + 14 = 0
0 + -10v = 6 + 14
-10v = 6 + 14

Combine like terms: 6 + 14 = 20
-10v = 20

Divide each side by '-10'.
v = -2

Simplifying
v = -2

See similar equations:

| -8x^4+8x^3-4x^2-16x+4=0 | | ln(7x-2)=5 | | -x^3+6x^2+8x=0 | | -5x+10=-86+3x | | 10sin^22x=5 | | Sinx=5/15 | | 16x^2-5x-4= | | 9a^2-6ab+b^2=0 | | 2x(x^2-9)=0 | | -16x+9y=3 | | 2x-5a+6.3=14.4 | | 16x^2-11x+4= | | x^3+6x^2-8x=0 | | 3x+x+4-6x=12 | | 4n^2+10n= | | 9a^2-6ab+b^2= | | 14+0.3333333x=40 | | y=3/5x-5/3 | | (3y-5z)(5y-6Z)= | | 12k^2+8k= | | x^3+3x^2-21x+7=0 | | 7x-9+6x=-9 | | 0.54x=-1.89 | | 0.54=-1.89 | | h=-16t^2+240t+1600 | | 8+4lnx=28 | | f(x)=2x^2-4x-1 | | (x+5)+(3x)+(x)=180 | | 30=x+2x+6x+3 | | 5+x=-5x+59 | | 3n^2+15n-150=0 | | 1+x+2x^3+3x^5=0 |

Equations solver categories